PENGARUH IMPLEMENTASI IFRS PADA LAPORAN KEUANGAN PERUSAHAAN DI INDONESIA - Taufiq Khaerudin (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2023)
Indonesia has implemented IFRS as a financial reporting standard following its implementation in multiple countries, resulting in the elimination of certain provisions of accounting standards. This change in concept will have an impact on the development of accounting in Indonesia. The aim of this research is to investigate the influence of IFRS adoption on financial reporting in Indonesia, despite the fact that it has both positive and negative consequences for Indonesian companies. A literature review was conducted using a descriptive qualitative approach, and secondary data sources were utilized. The research findings indicate that businesses in the industry can significantly demonstrate the effects of standard modifications, making it a more efficient standard. The principle-based standard has been created in the form of industry-specific accounting guidelines, which can be utilized as a reference for preparing financial statements for industrial companies.